Comparative Study On The Influence Of Mahalanobis Distance And Skin Color Range For Face Detection Using Adaboost. - Ong, Guang Yi; Zakaria, Zulhadi (2010)
This paper reports a comparative study on using Mahalanobis distance and skin color range to segment the skin Region.